Academician Viktor Sergeyevich Savelyev (1928–2013) (on the 95th anniversary of his birth) - Al. A. Kurygin; V. V. Semenov (Вестник хирургии имени И.И. Грекова, 2023)
Outstanding surgeon, scientist, teacher and organizer of healthcare, founder of a large surgical school, Hero of Socialist Labor (1988), academician of the USSR Academy of Medical Sciences (1974), RAMS (1991) and RAS (1997), laureate of the USSR State Prize (1975), the State Prize of the Russian Federation (1992), Demidov Prize (2002) and the A. N. Bakulev Prize (2002), Professor Viktor Sergeevich Savelyev was born on February 24, 1928 in the village of Pakhotny Ugol of the Bondarsky district of the Tambov region in the family of Sergei Dmitrievich Savelyev, a wood sawmill worker, and Olga Kuzminichna, a housewife. In 1945, Viktor Sergeevich entered the 2nd Moscow Medical Institute (now the Pirogov Russian National Research Medical University). After graduating in 1951, he studied in residency at the Department of Faculty Surgery, which was headed by the academician A. N. Bakulev, and was stayed at the department as an assistant. After defending his PhD thesis in 1955, he was appointed a teacher. In 1959, V. S. Savelyev successfully defended his doctoral dissertation, in 1961, he passed the academic title of Professor, in 1967, he was elected the head of the Department of Faculty Surgery. Viktor Sergeevich fully became the successor of A. N. Bakuleva and made the very great contribution to the development of domestic cardiac surgery. The works of V. S. Savelyev played a huge role in the formation and rapid development of vascular surgery. The clinic he headed has accumulated the world’s largest experience in the treatment of acute thrombosis and embolism of the main arteries. Viktor Sergeevich is rightfully one of the founders of modern Russian phlebology. He also made a significant contribution to the development of surgery of the stomach, intestines, bile ducts and pancreas. He was one of the first in the country to use organ-preserving operations on the stomach for complicated duodenal ulcer. Many of Viktor Sergeevich’s works were devoted to various aspects of postoperative management of patients, infusion therapy and parenteral nutrition, pathogenesis, diagnosis and treatment of sepsis. V. S. Savelyev and his students made a significant contribution to the development of abdominal endoscopy. V. S. Savelyev was a major organizer of domestic healthcare, for 34 years he held the post of the chief surgeon of the Ministry of Health of Russia. He was the Chairman of the Scientific Society of Surgeons of Russia (ROH), founder and president of the Russian Association of Phlebologists, editor-in-chief of journals «Thoracic and Cardiovascular Surgery» and «Phlebolymphology». Under his leadership and with his participation as the scientific consultant, 70 doctoral and 180 candidate dissertations were defended. He was the author and co-author of more than 500 scientific papers, including 24 monographs and manuals. The academician Viktor Sergeevich Savelyev died on December 25, 2013 and was buried in Moscow at the Troyekurovo Cemetery.